Food System Sustainability : Insights From duALIne / [electronic resource] - Esnouf, Catherine; Russel, Marie; Bricas, Nicolas (Cambridge : Cambridge University Press, 2013)
As western-style food systems extend further around the world, food sustainability is becoming an increasingly important issue. Such systems are not sustainable in terms of their consumption of resources, their impact on ecosystems or their effect on health and social inequality. From 2009 to 2011, the duALIne project, led by INRA and CIRAD, assembled a team of experts to investigate food systems downstream of the farm, from the farm gate, to consumption and the disposal of waste. Representing a diverse range of backgrounds spanning academia and the public and private sectors, the project aimed to review the international literature and identify major gaps in our knowledge. This book brings together its key conclusions and insights, presenting state-of-the-art research in food sustainability and identifying priority areas for further study. It will provide a valuable resource for researchers, decision-makers and stakeholders in the food industry.
Title from publisher's bibliographic system (viewed on 09 Oct 2015).
Keywords: Food industry and trade; Sustainable development